2019
DOI: 10.1039/c9sc03912k
|View full text |Cite|
|
Sign up to set email alerts
|

Laser cleavable probes for in situ multiplexed glycan detection by single cell mass spectrometry

Abstract: A single-cell MS approach for multiplexed glycan detection to investigate the relationship between drug resistance and glycans at a single-cell level and quantify multiple glycans, overcoming the limit of low ionization efficiency of glycans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Likewise, locations of ve other C]C bonds could be obtained. Therefore, the above evidence indicated that the detailed structure for one of the PC 38:6 isomers should be PC 16:0_22:6 (4,7,10,13,16,19).…”
Section: Application Of This Vaca Reaction In Structural Lipidomicsmentioning
confidence: 89%
See 1 more Smart Citation
“…Likewise, locations of ve other C]C bonds could be obtained. Therefore, the above evidence indicated that the detailed structure for one of the PC 38:6 isomers should be PC 16:0_22:6 (4,7,10,13,16,19).…”
Section: Application Of This Vaca Reaction In Structural Lipidomicsmentioning
confidence: 89%
“…16,17 The sensitivity and structural elucidation capabilities of mass spectrometry (MS) make it a preferred analytical technique for biomolecules. 5,6,[18][19][20][21][22][23] Some special methods for dissociation at the C]C bonds in MS were developed to locate their positions. [24][25][26][27][28] Meanwhile, selective chemical derivatizations or reactions of C]C bonds prior to MS analysis also emerged, as well as the electrochemical epoxidation in nano-electrospray ionization MS developed very recently.…”
Section: Introductionmentioning
confidence: 99%
“…90,91 Laser cleavable probes were developed for co-localization imaging of four types of glycans (i.e., mannose, Galb group, N-acetylglucosamine and sialic acids, Neu5Aca2-6Gal(NAc)-R) in breast cancerous and paracancerous tissues. 92 These successful innovations demonstrate the appeal and promise of MSI in the near future. There are other MSI techniques that are rarely applied in real-world clinical studies.…”
Section: Mass Spectrometry Imaging -"Where"mentioning
confidence: 96%
“…11 Recently, Han et al developed a method involving using laser cleavable lectin probes for glycan detection at the single cell level through mass spectrometry (MS)-based analysis. 12 These methods rely highly on the putative specicities of lectins towards glycoconjugates, however the in situ targets of the lectins are generally unknown thereby hindering the broader applications of these methods.…”
Section: Introductionmentioning
confidence: 99%